INDUSTRIES WASTE OBTAINED BY APODI CITY: DISPOSAL CHARACTERIZATION AND ITS USE IN RECYCLING PRACTICE BY SCHOOL COMMUNITY - Freire, Láiza Cristina Carlos; Oliveira, Mayk Henrique Gomes de; Oliveira, Dennis Rodrygo Marinho de; Alves, Leonardo Alcântara (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Problems generated by different forms of incorrect disposal of industrial wastes have grown considerably in recent years due to lack of managers awareness responsible for these industries. The present study aims to identify the most common industries residues originating from Apodi city as well as the disposal/correct handling of them, besides taking the class student awareness about the practice of using their own recycling waste from local industries. For this purpose, initially, a study was conducted by a preliminary waste management analysis in industries and identify them, as well as a workshop in a public school in the region.